2001
DOI: 10.1046/j.1537-2995.2001.41040550.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rejuvenation and frozenstorage on 42‐day‐old AS‐1 RBCs

Abstract: Forty-two-day-old AS-1 RBCs that have been rejuvenated and then frozen have more than 75 percent viability and normal oxygen delivery function. Rejuvenation of RBCs does not introduce additional safety hazards to blood transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…More recent studies have documented similar effects of rejuvenation–freeze–thaw–deglycerolization in red cells stored in modern additive solutions such as AS‐1, AS‐3 and AS‐5 . Rejuvenation results in supranormal 2,3‐DPG and ATP levels following storage in modern additive solutions, and comparable freeze–thaw deglycerolization, with recovery at 85%, and 24‐h in vivo survival at 75–85% . Most recently, Alessandro and colleagues have demonstrated that rejuvenation–freeze–thaw–deglycerolization in 42‐day‐old AS‐1 stored red cells upregulated glycolysis, increased levels of PPP intermediates and partially rescued glutathione biosynthesis when compared to 42‐day cells.…”
Section: Resultsmentioning
confidence: 97%
“…More recent studies have documented similar effects of rejuvenation–freeze–thaw–deglycerolization in red cells stored in modern additive solutions such as AS‐1, AS‐3 and AS‐5 . Rejuvenation results in supranormal 2,3‐DPG and ATP levels following storage in modern additive solutions, and comparable freeze–thaw deglycerolization, with recovery at 85%, and 24‐h in vivo survival at 75–85% . Most recently, Alessandro and colleagues have demonstrated that rejuvenation–freeze–thaw–deglycerolization in 42‐day‐old AS‐1 stored red cells upregulated glycolysis, increased levels of PPP intermediates and partially rescued glutathione biosynthesis when compared to 42‐day cells.…”
Section: Resultsmentioning
confidence: 97%
“…Reduced levels of 2,3‐DPG result in a decrease in the partial pressure of O 2 at 50% haemoglobin saturation or p50. This change may bring into question the efficiency of peripheral oxygen unloading of ≥14‐day‐old liquid stored RBCs following transfusion . While it is unknown whether oxygen delivery is significantly affected by transfusion of stored RBCs, immediate and significant 2,3‐DPG concentration deficit in‐vivo in patients receiving blood transfusions after surgery do occur.…”
Section: Introductionmentioning
confidence: 99%
“…Ex‐vivo rejuvenation of allogeneic RBCs, with a solution containing sodium pyruvate, inosine, adenine and sodium phosphates, increases the levels of ATP and 2,3‐DPG and increases the p50 of stored RBCs by right‐shifting the Oxyhaemoglobin Dissociation Curve towards a state where disassociation of oxygen from haemoglobin is more likely to occur . This is represented by a higher RBC Oxygen Release Capacity (ORC), or the per cent of oxygen removed from haemoglobin across the arterial (100 mmHg O 2 )–venous (40 mmHg O 2 ) pressure gradient .…”
Section: Introductionmentioning
confidence: 99%
“…RBCs stored in preservative solutions at refrigerated temperatures undergo various biochemical changes. Significant decreases in 2,3‐DPG and ATP after 2 weeks of refrigerated storage have been observed 1,2 . The decrease in 2,3‐DPG has been associated with the RBC's inability to deliver oxygen to the tissue.…”
mentioning
confidence: 99%
“…12.0 µmol/gHb at collection) fall to almost zero 1 . Studies of rejuvenation of RBCs stored in nutrient AS have demonstrated excellent results 2‐4 . The purpose of this study was to assess the effects of REJUVESOL treatment and cryopreservation of NUTRICEL (AS‐3) RBCs after 42 days of liquid storage.…”
mentioning
confidence: 99%